AN ANALYTICAL FRAMEWORK FOR CHINA’S SMART CITIES ECONOMY - Salih M. Sahi (Scholar Express Journal, 2022)
Smart cities are critical to country development. Several nations made significant investments in constructing smart cities to provide maintainable living in recent years. China has developed mature core technological services and platformsof applications, and associated technologies are extensively employed in economics, government, and everyday life. This study provides empirical insights into smart city development at the local level in China, as well as the challenges that it faces and the larger implications that it has. The major goal of the study is to look at the possible influence of smart city deployment on the Chinese economy. The rapid advancement of advanced technologies and their application have a significant impact on the development of smart cities. The smart economy is a major aspect of a Smart City. We review the evidence that smart city is having a large effect on the economy. This work used a literary survey to collect data and information from different resources. The approach relied on international organizations' statistics on the smart city economic performance correlation to obtain smart data. Specific data sources belonging to the latter category included the International Business Machines (IBM) ; Smart City Research Institute; Deloitte.com; Qianzhan Industry Research Institute (QIRI) ;and The Ministry of Industry and Information Technology of China (MIIT)
Keywords: Smart city; Digital Economy; knowledge economy; China